GoUNESCO: achieving strategic growth. Issue 2 (17th May 2021) - Chejarla, Kalyana C; Chatterjee, Sandeep
Abstract : Learning Outcomes: The case provides learning opportunities in strategy, planning and control in a social entrepreneurial setting. Following are the learning objectives of this case discussion: learn to develop a Strategic Service Vision (SSV) framework ; appreciate scalability challenges specific to service organizations; evaluate franchising model as a growth enabler; and understand the approach to internationalization as a growth strategy. Case Overview/Synopsis: GoUNESCO is a not-for-profit startup formed in January 2012, with an objective of providing platform for laypersons to engage with places of heritage value. Eight years into existence, in February 2019 GoUNESCO was experiencing substantial growth and faced need for pursuing alternate growth models that do not demand a lot of organizational bandwidth. Ajay Reddy, the founder of GoUNESCO was piloting "franchising" as a domestic growth strategy. He was keen on evaluating fitment of "franchising" (both for domestic and international expansion) in his strategic service vision. He wanted to understand what would be changes required in the strategic service vision on account of 'franchising', and decide whether those changes were acceptable or not. Complexity Academic Level: The case can be positioned in strategy, service and/or operations management introduction courses for both full-time or Executive MBA students. This case is also quite relevant in Entrepreneurship (or Social Entrepreneurship in particular) courses. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 11: Strategy